COMPARATIVE ANALYSIS OF SETTLEMENT OF DISPUTES WITH THE PARTICIPATION OF A JUDGE AND WITH THE HELP OF MEDIATION - Токарєва, Ксенія Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the article is to define the criteria and compare the main aspects of the essence of the dispute resolution procedure with the participation of a judge and the mediation procedure. To achieve this goal, a set of modern general and special methods was used: analysis, synthesis, comparative law, generalization, etc. Through the use of such methods, the main differences and common features of the studied concepts were identified, and ways to improve them were proposed. Results: the dispute settlement procedure with the participation of a judge and the process of mediation are significantly different, so they are not identifiable. Dispute resolution with the participation of a judge is a procedure close to mediation, a hybrid tool integrated into the judicial system. The criteria for distinguishing the studied concepts are: their essence, the degree of state regulation, timing, participants in the procedure, the role and legal status of the mediator, the grounds for conducting and terminating the procedure. Among the common features: the procedure, the principles of implementation (voluntariness, independence, confidentiality, neutrality of the mediator, etc.). The need to create a special law on mediation and expand the powers of public administration bodies and their officials remains relevant. Discussion: procedural legal acts, which regulate the dispute settlement procedure with the participation of a judge, require clarification of the powers of judges during this procedure. The condition of dissemination and use of conciliation procedures in the administrative process remains unsatisfactory and requires a new approach, changing existing stereotypes about the authoritarianism of public authority. The development of a system of mechanisms for alternative resolution of administrative and legal disputes requires further thorough scientific research.